EFEK ANTIINFLAMASI INFUSA RIMPANG TEMU PUTIH (Curcuma zedoaria (Berg) Roscoe) PADA TIKUS YANG DIINDUKSI KARAGENIN - Tanti Azizah Sujono; Raudatul Patimah; Ratna Yuliani (Biomedika, 2012)
In-flammation is the bodys reaction to foreign substances that enter the body with signs of redness, heat, swelling, pain, and impaired organ functions. Curcuma rhizome including medicinal plants that have properties relieve the pain and inflammation of the skin. The purpose of this research was to examine the anti-iflammation effect of Curcuma zedoaria (Berg) Roscoe Rhizome infusion on carrageenan induced paw edema in rats. This research used experimental method with completely randomized design. Twenty five healthy Wistar male rats, 2-3 months old and 150-250 g divided into five groups and each group consist of 5 rats. Rats in group I that served as negative control were given 2.5 mL/200gbw of aquadest. Rats in group II as positive control were given sodium diclofenac with dose of 6.75 mg/kgbw. Group III, IV, and V were given Curcuma zedoaria (Berg) Roscoe Rhizome infusion with dose of 0.625, 1.250 and 2.500 g/kgbw, respectively. Treatments were given per oral 1 hour before injection of 0.1 ml carrageenan 1% subplantar. Rat paw edema volume was measured before and after carrageenan injection. The measurement was done every 0.5 hour for 6 hours observation. Area Under the Curve (AUC) that is calculated from paw edema volume data, was use to calculate percentage of anti-inflammatory effect. Data were analyzed with one way Anova and Least Signifi cant Difference with confi dence level 95%. Infusion of Curcuma zedoaria Rhizome with doses of 0,625, 1,250, and 2,500 g/kgbw had anti-inflammatory effect in Wistar male rats which were induced by Carrageenan 1%. Percentage of anti-inflammation effect (44,16+5,11)%, (48,70+7,05)%, (59,09+9,61)% respectively and the effects were equivalent with positive control.Key words: Anti-inflammation, Curcuma zedoaria (Berg) Roscoe, infusion, Carrageenan.